(untitled) (Indian Journal of Animal Production and Management, 2014)
The present study was carried out to evaluate the effect of water restriction on broilers performance, supplemented with anti-stress preparation. A total of 500 Ven-Cobb broiler chicks were divided into five equal groups, with two replicates, of 50 birds each and were subjected to uniform feeding and managemental practices. Broilers in control group (T0) received ad-lib water, while broilers in T1 and T2 groups were subjected to two and four hours water restriction respectively. The broilers of T3 and T4 groups received anti-stress i.e. vitamin C, vitamin E and selenium (Vit.C + Vit.E + Se) preparation @ 2 gm per kg of feed subjected to two and four hours water restriction respectively. No significant difference was observed in growth performance of broilers among different treatment groups. The broilers receiving anti-stress preparation in the diet performed relatively better.